Code of Ethics of the State of Rahmatan: Formulating A Constitutional Profile Based on Islamic Sharia Maqashid - Ahmad Abdullatif; Marliang Marliang; Rahman Syamsuddin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The global political moral crisis characterized by structural corruption, social inequality, identity conflicts, and the degradation of the rule of law shows that the modern state paradigm of the rule of law that emphasizes formal legality has not been fully able to realize substantive justice and the public good. This research aims to formulate the Rahmatan State Code of Ethics as a constitutional profile based on maqāṣid al-syarī'ah in order to present an ethical, humanist, and just state model. This research uses a qualitative approach with juridical-normative and philosophical methods through the study of the constitution, maqāṣid al-syarī'ah literature, and modern constitutional theory. The results of the study show that the concept of the State of Rahmatan can be formulated as an ethical constitutional paradigm that places maqāṣid as the moral foundation for the administration of power. The constitutional profile of the state of rahmatan is formulated through the five pillars of maqāṣid, namely the protection of religion, soul, intellect, descendants, and property, which is compatible with the principles of modern human rights and the values of Pancasila in the 1945 Constitution. The Rahmatan State Code of Ethics serves as a constitutional moral guideline to close the gap between formal legality and moral legitimacy, so that the administration of the state is not only legally legal, but also substantively fair and humanely dignified.